(untitled) (Fiep Bulletin - online, 2012)
The body mechanics is a field of study that relates the static and dynamic forces that act on the human body. The optimal alignment of the body is related to a series of factors and difficult to achieve in all aspects, but it is standard for the meaning of which is directing efforts to obtain such an alignment. Poor posture is a faulty relationship between the segments of the body where a balance is less efficient on its structure. So observe and analyze the changes that such a stance entails erroneous, it is unquestionably important, especially when it comes to children. For this situation the objective of this study is to evaluate the posture of children in the fourth series of the first private education in the region of Ponta Grossa - PR, emphasizing segments of which the incidence of changes was greater than the ideal position. This goal is realized by means of a prospective, applied, descriptive, conducted with 883 children (n = 883), elementary school special education institutions of the city of Ponta Grossa. The postural analysis was done visually by trained, with observation of the previous views, side, right and left, and later. Postural changes found, as well as the personal data of the volunteers were recorded and later presented in a descriptive analysis. This led to the conclusion that the major changes found in the analysis using the previous view, were: 29.56% higher left shoulder, right shoulder high 25.48%, 38.84% knee genu valgus and knee rotated inward 23.56 %. From these results, it was possible to conclude the presence of changes in prevalence of upper limb segment (shoulder high and uneven), lower limbs (knee valgus and rotated inside) with higher values over the range considered normal.